Saponin accumulation in the seedling root of Panax notoginseng - Zhang Yingjun; Xu Min; Chen Keke; Zhu Hongtao; Wang Dong; Yang Chongren (BMC, 2011)
Abstract Background Panax notoginseng is an important Chinese medicinal plant. Dammarene-type triterpenoid saponins are main pharmacologically effective compounds in P. notoginseng. This study aims to investigate the formation and accumulation of saponins in P. notoginseng roots during germination and juvenile stage. Methods P. notoginseng seeds were collected and stored in wet sand. After germination, the seedlings were transplanted into a soil nursery bed and cultivated for one year. During this period, samples were collected every month and the concentrations of ginsengnosides Rg1, Re, Rb1, Rd and notoginsengnoside R1 were determined by HPLC. Results There was little saponin in the P. notoginseng seed. The chemical composition of seed was different from that of root. After germination, Rb1, Rg1, Re, Rd and R1 appeared successively in the seedling root. And in the five-month-old root, all these five main saponins came into existence. The accumulation of saponins in P. notoginseng root was affected by seasons. Conclusion The accumulation of saponins showed a time-dependent increase after germination of P. notoginseng.